Prevalence of Virulence Genes Associated with Diarrheagenic Pathotypes of Escherichia coli Isolates from Water, Sediment, Fish, and Crab in Aby Lagoon, Côte d’Ivoire - Ollo Kambire; Ama Antoinette Adingra; Konan Mathurin Yao; Rose Koffi-Nevry (International Journal of Microbiology)
This study was conducted to characterize virulence genes of Escherichia coli isolates from water, sediment, fish, and crab in Aby Lagoon. Serogrouping was performed by EPEC antisera in 113 E. coli strains. The presence of diarrhea-associated genes (eae, stx, AggR, elt, and est) was assessed by multiplex PCR using specific primers. Based on the multiplex PCR, sixty-two isolates (42 from water, 19 from sediment, and 1 from crab) were positive for virulence genes, including 34 positive for elt (ETEC), 46 positive for est (ETEC), 24 positive for both elt and est, 6 positive for stx (EHEC), 1 positive for both stx + est, and 1 positive for both stx + elt. Genes eae (EPEC) and AggR (EAEC) were not detected. Nine serogroups (O114, O127, O55, O111, O86, O119, O126, O128, and O142) were identified. This study revealed the presence of diarrheagenic and nondiarrheagenic E. coli and potential public health risks if fishery products are not appropriately cooked.